The Extended Body: On Aging, Disability, and Well-being - Reynolds, Joel Michael (The Hastings Center report, 2018)
Insofar as many older adults fit some definition of disability, disability studies and gerontology would seem to have common interests and goals. However, there has been little discussion between these fields. The aim of this paper is to open up the insights of disability studies as well as philosophy of disability to discussions in gerontology. In doing so, I hope to contribute to thinking about the good life in late life by more critically reflecting upon the meaning of the body, ability, and the variability of each. My central argument is that we should conceptualize age-associated bodily variations and abilities not in terms of individual capacity, but in terms of what I call “the extended body.” It is in light of the meaning of embodiment and ability in general that we must think differently and more capaciously about the meaning of late life in particular.